Implementasi Metode Waterfall pada Sistem Penjualan Berbasis Website - Supriatiningsih; Supriatiningsih, Supriatiningsih; Dwi Mulyanto, Joko (Informatics and Computer Engineering Journal, 2022)
All people today feel the impact of the sophistication of increasingly advanced information technology. Technological advances make it easy for people to find various information via the internet. In the business field, the internet is the right place so that the business that is run has good progress. One of the services provided for business people is the existence of an e-commerce website. Through e-commerce, we can make online ordering, buying, selling, and marketing transactions. Ocean Indah Furniture is a business entity engaged in the furniture sector that provides various kinds of household furniture. So far, the information system used is still manual, such as processing product data which is still written in computer books and, and transaction processing that can be done on the spot. The contents include product data, product categories, shipping facilities, payments, member data, filling out testimonial forms, ordering online and confirming payments. For this reason, it is hoped that this system can achieve effective and efficient sales, expand the scope of marketing, and increase the amount of revenue.